Essays on competitive and strategic bidding in multi-object auctions - Finster, S (2022)
This thesis addresses four important issues in multi-object auction markets, focusing on a theory of strategic bidding and corresponding empirical evidence, on questions of equilibrium existence with distributional preferences, and on the equivalence of market objectives.